(untitled) (Comprehensive Journal of Science, 2025)
Study Title: Psychological Stress and its Relationship with the Level of Job Burnout among Basic Education Teachers: A Field Study in Private Education Schools in Al Ajaylat City. Objective: This study aimed to reveal the nature of the correlational relationship between psychological stress and job burnout (in its three dimensions) among basic education teachers in private schools in Al Ajaylat City, and to examine differences based on gender and years of experience. Methodology and Sample: The study adopted the descriptive-analytical method. The study sample consisted of (550) male and female teachers from private schools in Al Ajaylat City. A validated questionnaire containing stress and burnout scales was used as the main instrument. Key Findings: The statistical analyses using the SPSS program yielded the following main results: 1. The level of psychological stress among teachers was found to be High (X = 3.95), with the highest pressure originating from "workload" and "financial stress". 2. The level of job burnout was Medium to High (X = 3.80), dominated by the Emotional Exhaustion dimension. 3. A strong, positive, and statistically significant correlation was found between psychological stress and job burnout (r = 0.78, p < 0.01), confirming that stress is a major predictor of burnout. 4. Statistically significant differences in job burnout were attributed to the gender variable, favoring females (higher burnout levels). 5. Statistically significant differences in job burnout were attributed to the years of experience variable, favoring less experienced teachers (less than 5 years). Main Recommendations: The study recommended that educational administrations must intervene by restructuring the workload, providing better financial support, and activating professional psychological counseling programs and mentorship for new teachers to mitigate job burnout.